A Production Analysis of Dry Onion Powder from the Water Perspective - Oyelayo Ajamu Oyedele; Olusegun Adeoti; Funke Florence Akinola (Turkish Journal of Agriculture: Food Science and Technology)
Nigeria’s dry onion production amounted to 1.38× 106 metric tonnes (t) in 2020. Roughly 50% of yearly production do not reach the table. An option lies in converting fresh dry onions to dry onion powder to mitigate postharvest losses. This study explores the possibility of producing dry onion powder from fresh dry onions using a pre-tested locally fabricated direct-mode solar tent dryer. The outcome of processing revealed a product yield of 8.09%, while there was no statistically significant difference between the measured proximate contents of powder and fresh dry onions (t(28)=0.04, p=0.97, two-tailed; eta square=5.71 × 10-5). Overall, the production of dry onion powder was not water neutral. About 4.5 cubic metres (m3) of freshwater per tonne of cleaned onions were needed during processing. Dry onion powder production (from field to table) freshwater use amounted to 31879.6 m3/t. Converting 40 - 60% of national average dry onion production (2000-2020) to dry onion powder would consume 14.05 - 21.08 × 109 m3 of Nigeria’s freshwater. This study affirms that dry onion powder production is technically feasible and can help to minimise dry onion production postharvest losses in Nigeria.